Productive practices of Hotel Management System using usability approach: a case study - Pa, Noraini Che; Hassan, Sa’adah; Husin, Nur Shuhada; Ban, Ainita (American Scientific Publishers, 2016)
Hospitality industry encompasses a variety of service industries that include food service, tourism and hotels. Nowadays, hospitality industry has turned to IT as a way to cope with an environment characterized by globalization, competition, high client turnover, and rising guest expectations. Commonly in hotel field, Hotel Management System (HMS) is the main component used to handle the operation of all major tasks such as reservation, room check-in, room check-out and all others monitoring tasks. This work aims to evaluate the usability aspect of HMS and its relation to productive practices. Usability is one of the important attributes for system quality, thus it does affect the business productivity. We focused on the evaluation of six usability attributes which adopted from ISO/IEC 25010 and Software Usability Measurement Inventory (SUMI) which are effectiveness, efficiency, affect, helpfulness, control, and learnability. It is limited to five common tasks in HMS that ordinarily perform by the users. There are two stages of usability testing were conducted in this study, which are preliminary usability testing to evaluate the usability of the current HMS, and post survey usability testing on the improve version of the HMS. The improve version of the HMS was develop as a prototype based on the preliminary usability testing result where some usability improvement was adding to the prototype. Based on the study conducted, it is found that the productivity in the hotel operation has potential to be increased by improving the usability of the HMS.